Adaptation and the legal basis for the civil liability of car showroom owners: Comparative analysis study - Tahsin Hamad Smael; Abdullah Khairi Azeez (QALAAI ZANIST JOURNAL, 2024)
Car showrooms are the places where cars are bought and sold, and these works are carried out by the showroom owners and their employees, and their work may be diverse, such as receiving and displaying cars and working as a mediator for the conclusion of sales and purchase contracts, where the procedures and responsibility differ in them. The damage may occur while the car is in the showroom or a breach of the terms of the contracts in which it is concluded, whether the damage was caused by the owners of the showroom themselves or by its employees, and for that reason, the aim of this study was embodied in stating the legal adaptation of this responsibility in the light of the general rules of civil liability. In the Iraqi civil law and comparative laws such as the Egyptian civil law and the Jordanian civil law, as well as through the Iraqi law of significance and commercial laws for comparative laws, as well as determining the legal basis for this liability. To contain these topics, we divided the study into two sections. In the first section, we dealt with the legal conditioning of the liability of exhibition owners in two stages, the stage before and during the sale of cars, and the stage of establishing his responsibility for the work and actions of the exhibition workers. In the second topic, we tried to determine the legal basis for this responsibility in both the pre-sale and during the sale phase, and concerning the work and actions of the two workers in it as well, and we concluded the study with our conclusions and recommendations.